PENERAPAN TERUMBU KARANG BUATAN (RUMPON) DI PERAIRAN KUTAI KARTANEGARA KALIMANTAN TIMUR - Riyadi, Agung (Jurnal Hidrosfir Indonesia, 2010)
Artificial reef (rumpon) are tools in the form fish collecting objects or structures that are designed made from natural or artificial materials that are placed permanently in marine waters. Many oil rigde spread in coastal area. Majority of fisherman from Kutai Kartanegara catch a fish around oil ridge and very dangerous. The Application of artificial reef technology as coral reefs have been set at Kutai Kartanegera waters in 2009. Activities are particularly in assessment site selection survey for deployment the artificial reef depand the quality and depth water. Artificial reef made of concrete with a total 60 pieces and has a size of 2 x 2.5 meters. The results of physical and chemical analysis such as water temperature, depth, salinity, turbidity, based material and dissolved oxygen in the normal condition. The dominat of sediment in a sand bed is muddy and has a marine topography a slope, because there is still considerable influence of the Mahakam delta. There are six potential locations for mooring artificial reef at position UTM 1.555000/9975100; 2.555823/9978221;3.559711/9981510;4.562515/9986117;5.558448/9991855; 6.557506/9987513. Artificial reef placement depths ranging 15 - 25 meters.